Budaya yang Terlupa, Tanah Air yang Terabaikan: Ketika Budaya Lokal Tak Lagi Jadi Pilihan - Novia Layla Handi; Katalina Arumdani; Dea Putri Dwi Setyowati; Citra Dwi Yuniar; Tasya Cahya Ananda; Tegar Anggoro Bramasto (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Indonesian local culture, which is the heritage of the younger generation as a national identity, is now facing serious threats due to globalization and modernization. The young generation in this era of globalization tends to be indifferent and even abandon traditional cultural values and prefer foreign cultures that are considered cooler and more modern. This can certainly make the Indonesian nation an identity crisis. Therefore, this research was carried out with the aim of analyzing the extent to which local culture began to be abandoned by the Indonesian people as a young generation. The research method used is a literature study. This method is done by analyzing various sources such as scientific journals, books, and relevant articles. Then, the results of this literature study review show that local culture has been degraded due to the dominance of global culture. This will certainly have implications for the weakening of the nation's identity. The preservation of local culture requires the active role of education and digital media as a means of spreading the nation's noble values.